2013
DOI: 10.5455/ijmsph.2013.2.104-109
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and risky sexual behaviour on HIV/AIDS amongst commercial motorcyclists in Osogbo, Osun State, South Western Nigeria

Abstract: Background: There has been global concern regarding HIV/AIDS epidemic particularly in developing countries. The magnitude of the epidemic result not only in the loss of human life but enormous financial burden to health care system and loss of productivity to the country. It has created unparalleled social and medical challenge. Aims & Objective: This study assesses the knowledge, attitude and risky sexual practices on HIV/AIDS among commercial motorcyclist in Osogbo, Osun States. Material and Methods: A cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…This high level of knowledge could be due to different national campaigns which have been undertaken in Tanzania in the past two decades, to increase public awareness of HIV [23]. Our ndings were comparable with that obtained in another study which was conducted in Nigeria, which showed that majority of commercial motorcyclists were aware of HIV and the risk of getting infected due to their occupation [24]. Our study also reported that majority of BBRs were aware that sexual intercourse is the major means of HIV transmission like in the study conducted in Kenya [25].…”
Section: Discussionsupporting
confidence: 84%
“…This high level of knowledge could be due to different national campaigns which have been undertaken in Tanzania in the past two decades, to increase public awareness of HIV [23]. Our ndings were comparable with that obtained in another study which was conducted in Nigeria, which showed that majority of commercial motorcyclists were aware of HIV and the risk of getting infected due to their occupation [24]. Our study also reported that majority of BBRs were aware that sexual intercourse is the major means of HIV transmission like in the study conducted in Kenya [25].…”
Section: Discussionsupporting
confidence: 84%